Pengaruh Gaya Kepemimpinan dan Motivasi Kerja Terhadap Kinerja Karyawan pada Cabang PT. Central Mega Perdana Pekanbaru - Sehani Sehani; Ade Fitri (Al-Manar Journal of Accountancy and Business Studies, 2024)
This study aims to determine the effect of the Organizational Change Capability dimension which has the variables Learning Capability, Process Capability and Context Capability on performance at PT. Permodalan Ekonomi Rakyat Provinsi Riau in Pekanbaru city. This type of research is quantitative descriptive research with a sample of 87 respondents who are all employees of PT. Permodalan Ekonomi Rakyat Provinsi Riau in Pekanbaru city who have met the sample criteria. The results of this study indicate that partially Process Capability and Context Capability have a positive and significant effect on the performance of PT. Permodalan Ekonomi Rakyat Provinsi Riau in Pekanbaru city. The Determination Coefficient (R2) with an adjusted R square value of 0.565 or 56.5% indicates that learning capability, process capability, and context capability have an effect of 56.5% on employee performance, while the remaining 43.5% is influenced by other variables not used in this study.